Postmodernity, Sociology and Religion
XIV, 224 p.
Keywords: This topical collection of eleven commissioned essays by well-established contributors from sociology, religious studies and theology, is one of the first treatments of the relationship between postmodernity and religion from a sociological perspective. The essays cover a diversity of interests, but treat postmodernity in terms of its implications for the self, the New Age and theology, particularly Catholicism and Judaism. Two of the essays are original appraisals of two important French writers on religion: Jean-Luc Marion and Daniele Hervieu-Leger.